PEMBUATAN SABUN PADAT TRANSPARAN MENGGUNAKAN MINYAK KELAPA SAWIT (Palm oil) DENGAN PENAMBAHAN BAHAN AKTIF EKSTRAK TEH PUTIH (Camellia sinensis) - Widyasanti, Asri; Farddani, Chintya Listiarsi; Rohdiana, Dadan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
Transparent soap is a kind of solid soap. The addition of white tea extracts could be expected to increase theadvantageof transparent soap. The purpose of this research was to determine process and formulation for themaking of transparent solid soap using palm oil based with addition white tea extracts and its effect to thecharacterictics of transparent solid soap. This reasearch was used laboratory experimental method using descriptiveanalysis. The treatment of this reasearch were addition of white tea extracts using concentrations 1% (w/v) withthe addition of A= 0% (w/v), B=0.5% (w/v), C=1.0% (w/v), and D=1.5% (w/v). Parameters observed wereorganoleptic, chemical properties, antibacterial activity, hardness, and stability of foam. Organoleptic test resultsshowed that panelists prefer soap treatment B with a percentage of 36.67%. The chemical properties of this soapwas in accordance with SNI solid soap No.06-3532-1994, except amount of fatty acids. The value of water contentand evaporated substance was 12.17%, the content of free alkali was 0.101%, the content of unsaponifiedfraction was 2.10%, and the amount of fatty acid was 35.67%. pH value was in accordance ASTM D 1172-95 withpH value of 10. The value of hardness was 0.0091 mm/g/s, stability of foam was 39.08%, and antibacterialactivity with inhibition zone diameter was 11.28 mm. It proved that making transparent solid soap using a palmoil based and the addition of white tea extract as active ingredients could be applied by the community.Keywords:Transparant Solid Soap, Palm Oil, White Tea Extract